Eco-Brick Utilization as a Solution to Environmental Problems and Utilization of Plastic Waste in Jawisari Village - Erma Aulia Istiqomah; Nur Rahmaniyah Wijayanti; A’immatus Sa’diyah; Ivena Tiara Syafa; Eky Pradipta; Fitria Natasya Anjani; Layla Asyrotun Ni’mah; Faridabby Tsamarah Hannu; Lenni Khotimah Harahap (Universitas Kristen Indonesia Toraja, 2024)
The plastic waste problem in Indonesia, which is the second largest contributor in the world, prompts the need for innovative and sustainable solutions. One proposed solution is the utilization of plastic waste into ecobricks, which are eco-friendly bricks made from compacted plastic waste. The training program in Jawisari Village involved socialization and practice of ecobricking, aiming to raise community awareness about plastic waste management and provide practical skills. The activity successfully engaged the community, produced ecobricks, and is expected to create a cleaner and healthier environment.